2016
DOI: 10.1002/ardp.201600285
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Pyrazolines, Their Boron–Fluorine Complexes, and Investigation of Antibacterial, Antioxidant, and Enzyme Inhibition Activities

Abstract: New 3,5-disubstituted-2-pyrazoline derivatives (4-6), their boron-fluorine complexes (boron (3-(2'-aminophenyl),5-(2'-/3'-/4'-pyridyl)pyrazoline, BOAPPY) (7-9) and boron 1,2'-diazaflavone complex (BODAF) (11) were synthesized starting from azachalcones (1-3) to diazaflavone (10), respectively. Biological evaluation of compounds 4-9 and 11 showed remarkable antioxidant, antibacterial, and acetylcholinesterase and tyrosinase enzyme inhibition activities. All newly synthesized compounds 4-9 and 11 showed respecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
8
0
1
Order By: Relevance
“…In the previous studies, it was indicated that these compounds have significant pharmacological and biological activities . Many pyrazoline compounds are reported to possess a broad spectrum of biological activities such as antimicrobial, antidepressant, neuroprotective, anticonvulsant, anti‐inflammatory, analgesic, antitubercular, local anesthetic, hypoglycemic, hypotensive, insecticide, herbicide, and molluscicidal . In addition, the antioxidant properties of the newly synthesized pyrazoline group were also studied .…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, it was indicated that these compounds have significant pharmacological and biological activities . Many pyrazoline compounds are reported to possess a broad spectrum of biological activities such as antimicrobial, antidepressant, neuroprotective, anticonvulsant, anti‐inflammatory, analgesic, antitubercular, local anesthetic, hypoglycemic, hypotensive, insecticide, herbicide, and molluscicidal . In addition, the antioxidant properties of the newly synthesized pyrazoline group were also studied .…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used acid catalyst in the synthesis of 2pyrazolines is acetic acid (Scheme 4). [25][26][27]58] As shown in the scheme, chalconic compounds 4 a, 4 b, and 4 c undergo acetic acid-catalyzed cyclization with hyrazines 4 d, 4 e, and 4 f to yield 2-pyrazolines 4 g, 4 h, and 4 i, respectively. These reactions can be performed in two ways: i) acetic acid is used as solvent and catalyst, and ii) acetic acid is used as catalyst in the presence of a solvent.…”
Section: Acid-catalyzed Reactionmentioning
confidence: 99%
“…Çalışma kapsamında ilk olarak Claisen-Schmidt kondenzasyonu ile 3 adet kalkon bileşiği (1-3) [19,[29][30] ve bu bileşiklerin hidrazin hidratla asit katalizli Michael katılması reaksiyonuyla da moleküller arası halkalaşma ürünü olan 3 adet yeni 3,5disübstitüe-2-pirazolin türevi (4-6) sentezlenmiştir [31]. Elde edilen bileşiklerin yapıları FT-IR, 1 H-NMR, 13 C-NMR (APT) ve kütle spektral verileri kullanılarak aydınlatılmıştır.…”
Section: Tartışma Ve Sonuçlarunclassified